Contribution of Molecular Structure to Self-Assembling and Biological Properties of Bifunctional Lipid-Like 4-(N-Alkylpyridinium)-1,4-Dihydropyridines - Martins Rucins; Pavels Dimitrijevs; Klavs Pajuste; Oksana Petrichenko; Ludmila Jackevica; Anita Gulbe; Signe Kibilda; Krisjanis Smits; Mara Plotniece; Dace Tirzite; Karlis Pajuste; Arkadij Sobolev; et al. (MDPI AG, 2019)
The design of nanoparticle delivery materials possessing biological activities is an attractive strategy for the development of various therapies. In this study, 11 cationic amphiphilic 4-(N-alkylpyridinium)-1,4-dihydropyridine (1,4-DHP) derivatives differing in alkyl chain length and propargyl moiety/ties number and position were selected for the study of their self-assembling properties, evaluation of their cytotoxicity in vitro and toxicity on microorganisms, and the characterisation of their interaction with phospholipids. These lipid-like 1,4-DHPs have been earlier proposed as promising nanocarriers for DNA delivery. We have revealed that the mean diameter of freshly prepared nanoparticles varied from 58 to 513 nm, depending upon the 4-(N-alkylpyridinium)-1,4-DHP structure. Additionally, we have confirmed that only nanoparticles formed by 4-(N-dodecylpyridinium)-1,4-DHP derivatives 3 and 6, and by 4-(N-hexadecylpyridinium)-1,4-DHP derivatives 10 and 11 were stable after two weeks of storage. The nanoparticles of these compounds were found to be homogenous in size distribution, ranging from 124 to 221 nm. The polydispersity index (PDI) values of 1,4-DHPs samples 3, 6, 10, and 11 were in the range of 0.10 to 0.37. We also demonstrated that the nanoparticles formed by 4-(N-dodecylpyridinium)-1,4-DHP derivatives 3, 6, and 9, and 4-(N-hexadecylpyridinium)-1,4-DHP derivatives 10 and 11 had zeta-potentials from +26.07 mV (compound 6) to +62.80 mV (compound 11), indicating a strongly positive surface charge and confirming the relative electrostatic stability of these nanoparticle solutions. Transmission electron microscopy (TEM) images of nanoaggregates formed by 1,4-DHPs 3 and 11 confirmed liposome-like structures with diameters around 70 to 170 nm. The critical aggregation concentration (CAC) value interval for 4-(N-alkylpyridinium)-1,4-DHP was from 7.6 µM (compound 11) to 43.3 µM (compound 6). The tested 4-(N-alkylpyridinium)-1,4-DHP derivatives were able to quench the fluorescence of the binary 1,6-diphenyl-1,3,5-hexatriene (DPH)—1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) system, demonstrating hydrophobic interactions of 1,4-DHPs with phospholipids. Thus, 4-(N-dodecylpyridinium)-1,4-DHP derivative 3 quenched the fluorescence of the DPH–DPPC system more efficiently than the other 4-(N-alkylpyridinium)-1,4-DHP derivatives. Likewise the compound 3, also 4-(N-dodecylpyridinium)-1,4-DHP derivative 9 interacted with the phospholipids. Moreover, we have established that increasing the length of the alkyl chain at the quaternised nitrogen of the 4-(N-alkylpyridinium)-1,4-DHP molecule or the introduction of propargyl moieties in the 1,4-DHP molecule significantly influences the cytotoxicity on HT-1080 (human fibrosarcoma) and MH-22A (mouse hepatocarcinoma) cell lines, as well as the estimated basal cytotoxicity. Additionally, it was demonstrated that the toxicity of the 4-(N-alkylpyridinium)-1,4-DHP derivatives on the Gram-positive and Gram-negative bacteria species and eukaryotic microorganism depended on the presence of the alkyl chain length at the N-alkyl pyridinium moiety, as well as the number of propargyl groups. These lipid-like compounds may be proposed for the further development of drug formulations to be used in cancer treatment.